Evaluation of soybean oil additions in starter pig diets - R C Thaler; M E Johnston; G L Allee; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1986)
Two trials involving 420 weanling pigs (21+3 d) were conducted to determine the effects of additions of soybean oil (SO) on starter pig performance. Soybean oil additions of either 0, 1, 2, 3, 4, or 5% were made to the 1.25% lysine corn-soybean meal-dried whey basaI diet. In each trial, there were 7 pigs/pen and 5 replications. Data from the two trials were pooled except for feed efficiency (F/G) at 2-weeks, where a trial x treatment interaction existed. Average daily gain (ADG) and average daily feed intake (ADFI) were not affected by SO additions at 2 weeks but gains were numerically higher when 3% SO was added to starter diets. Feed efficiency in Trial 1 improved linearly (P<.001), whereas a cubic response (P<.05) in F/G with added levels of SO was observed in Trial 2. At 35 days, SO additions caused a linear improvement in ADG (P<.01), ADFI (P<.05) and F/G (P<.0001), with the highest numerical response in gain and feed intake at the 3% SO level. Metabolizable energy (ME) intake was not affected by dietary treatment, but was optimized at the 3% SO inclusion level. Based on these data, it appears that 21-d old pigs can utilize fat, and soy oil additions of between 3 and 5% are beneficial to starter pig performance.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Soybean oil; Starter pig